Perceptions of Affected Communities in Gresik Regency Following the Communication Campaign on the Development, Protection, and Management of the Brantas River Conducted by the Governor of East Java - Citra Paramita; V. Rudy Handoko; Enryco Budi Sayogo (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN-COMMUNITY OF RESEARCH LABORATORY, 2025)
This study examines the perceptions of affected communities in Gresik Regency following the communication campaign on the development, protection, and management of the Brantas River conducted by the Governor of East Java. The research is grounded in the concern that public communication on environmental governance does not always correspond with community experiences in affected areas, particularly where river pollution and environmental degradation remain visible. The objective of this study is to analyze community perceptions and identify the factors influencing those perceptions. This research employed a quantitative approach with an explanatory cross-sectional survey design involving 200 respondents drawn from communities living and working around the Brantas River area in Gresik Regency. Data were collected using a structured questionnaire with a Likert scale and analyzed through descriptive statistics and multiple linear regression. The findings indicate that community perceptions tend to be negative, with an average perception score of 2.43 out of 5; 70% of respondents showed negative perceptions, 20% neutral perceptions, and only 10% positive perceptions. Regression analysis reveals that trust in government is the strongest factor influencing perception, followed by the clarity of information and exposure to information, both of which have significant positive effects. In contrast, the experience of being affected by river-related environmental problems has a significant negative effect, while community participation does not show a statistically significant influence. These findings suggest that the effectiveness of environmental communication campaigns depends not only on message dissemination but also on public trust, clarity of communication, and the government’s ability to demonstrate tangible improvements in river conditions.